Case-matched study of lesser versus greater curvature approach in laparoscopic Warshaw pancreatectomy - Müller, Philip C.; Müller, Sascha A.; Steinemann, Daniel (The American journal of surgery, 2017)
Background In laparoscopic distal pancreatectomy (LapDP), the pancreas is accessed in a greater curvature approach (GCA). The lesser curvature approach (LCA) has been proposed in underweight patients. The study investigated the feasibility of LCA irrespective of the body mass index (BMI). Methods This retrospective study included consecutive patients scheduled to undergo LapDP with the LCA. A matched cohort (1:1) underwent GCA. Spleen preservation was performed using the Warshaw technique. Splenic perfusion was intraoperatively assessed by indocyanine green (ICG) angiography. Results The LCA with LapDP was successful in 12/15 patients. In 2 cases, LCA had to be converted to GCA and in 1 patient to open surgery. The cohorts were well matched in sex (P = 1.0), age (P = .67), indication (P = 1.0), and median BMI (23.4 kg/m2 vs 24.8 kg/m2, P = .41). Splenic preservation was achieved in 14/15 patients with LCA and 4/15 patients with GCA (P = .33). In all LCA cases, ICG angiography indicated sufficient spleen perfusion. The groups had similar morbidity (P = 1.0) and hospital stay (P = .74). Conclusions LCA was feasible in 80% irrespective of BMI and provided an excellent field of exposure. ICG angiography was feasible in the Warshaw technique. Its reliability should be evaluated in prospective studies.